The Teacher’s Work Groups and Work Motivation on Teacher’s Professional Competence - Rumnah, Rumnah; Lian, Bukman; Wardiah, Dessy (Journal of Social Work and Science Education, 2023)
This paper examined is there an effect of the teacher’s work group activities and work motivation partially and simultaneously on the teacher’s professional competence? this study is a quantitative research design, by testing the independent variables on the dependent variable. We used purposive sampling technique to determine the sample. The main sample used in the implementation of this research were 66 people who came from 5 primary schools in Lempuing Jaya District. In this study the main source used was the questionnaire technique, while for additional data it was carried out by utilizing information that was already available through documentation. The data obtained from the implementation of the research was then tested so that the results achieved could be described, and conclusions could be drawn from the tests that had been carried out. Testing is carried out in two stages, prerequisites and actual testing to prove the acceptance or rejection of the research hypothesis. The results obtained indicate that there is a positive and significant effect of teacher work group activities and work motivation both partially and jointly on the professional competence of teachers